2018
DOI: 10.3354/meps12223
|View full text |Cite
|
Sign up to set email alerts
|

Facultative oligohaline habitat use in a mobile fish inferred from scale chemistry

Abstract: Sustainability within the fisheries of the commercially important European whelk Buccinum undatum has become a major concern because of over-exploitation and increased landings in many European coastal shelf seas due to the expansion of export markets to East Asian countries. Current management of B. undatum populations is difficult to achieve as several life history traits are problematic to accurately monitor. The current method of age determination for stock assessment has a low success rate and focuses on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 53 publications
(80 reference statements)
1
14
0
Order By: Relevance
“…Despite the well‐documented presence of mature adult tarpon in freshwaters (Babcock, ; Dimock & Dimock, ; Koenig et al, ), much of the scientific literature describes adult tarpon habitat as mainly shallow coastal waters, bays and estuaries, with only an occasional reference to freshwaters (Moyle & Cech, ; Robins & Ray, ). A recent study based on elements and isotopic ratios in tarpon scales (Seeley & Walther, ) showed that tarpon spent on average 42 ± 34% of life histories within oligohaline habitats, while another study using tarpon eye lens showed 100% juvenile habitat in upper estuarine habitat (Kurth, Peebles, & Stallings, ). Our study reinforced this concept by showing that some adult tarpon used freshwaters extensively (Supporting Information), while others rarely travelled to freshwater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the well‐documented presence of mature adult tarpon in freshwaters (Babcock, ; Dimock & Dimock, ; Koenig et al, ), much of the scientific literature describes adult tarpon habitat as mainly shallow coastal waters, bays and estuaries, with only an occasional reference to freshwaters (Moyle & Cech, ; Robins & Ray, ). A recent study based on elements and isotopic ratios in tarpon scales (Seeley & Walther, ) showed that tarpon spent on average 42 ± 34% of life histories within oligohaline habitats, while another study using tarpon eye lens showed 100% juvenile habitat in upper estuarine habitat (Kurth, Peebles, & Stallings, ). Our study reinforced this concept by showing that some adult tarpon used freshwaters extensively (Supporting Information), while others rarely travelled to freshwater.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the well-documented presence of mature adult tarpon in freshwaters (Babcock, 1921a;Dimock & Dimock, 1912;Koenig et al, 1976), much of the scientific literature describes adult tarpon habitat as mainly shallow coastal waters, bays and estuaries, with only an occasional reference to freshwaters (Moyle & Cech, 1988;Robins & Ray, 1986). A recent study based on elements and isotopic ratios in tarpon scales (Seeley & Walther, 2018) Williams & Jones, 1994), and rapid movements between freshwaters and ocean environments may reduce the infections of pathogens (Westerdahl et al, 2014). Babcock (1951) stated that tarpon might use the freshwater habitat to get rid of remoras and sea lice (Nerocila acuminate, Cymothoidae) since the remoras and sea lice cannot survive the freshwater.…”
Section: Estuarine and Riverine Utilizationmentioning
confidence: 99%
“…Red Drum residency within oligohaline portions of estuaries has been poorly studied and these salinities are below Red Drum isosmotic equilibrium (Crocker et al 1983;Forsberg and Neill 1997;Watson et al 2014). While thresholds cannot determine precise salinities, they provide probable conservative estimates of inhabited salinity ranges, especially when results are robust across variable thresholds (Nims and Walther 2014;Seeley and Walther 2018), as was the case here. While we are confident that juvenile Red Drum otolith Sr:Ca can reliably discern oligohaline waters from meso-polyhailne ones, we do believe that growth and maturation likely affected otolith Sr:Ca ratios in adult Red Drum and discuss these ontogenetic implications in the following section.…”
Section: Considerations and Caveatsmentioning
confidence: 62%
“…Furthermore, otolith and water Sr:Ca in Mobile Bay does not exhibit changes beyond salinities of 10 (Nelson and Powers 2020a). This asymptotic Sr:Ca relationship is typical among estuaries; however, differences in oligohaline and mesopolyhaline salinity ranges are discernable with this proxy (Walther and Limburg 2012;Seeley and Walther 2018;Nelson and Powers 2020a). The choice of an oligohaline threshold was also physiologically and ecologically relevant.…”
Section: Considerations and Caveatsmentioning
confidence: 80%
“…In addition, structures like vertebrae provide an opportunity to study cartilaginous fishes that lack otoliths. Non-lethal methods using spines and scales have been employed to study lifetime movement patterns and assess stock structure in many species (Rude et al, 2014;Seeley et al, 2015;Seeley and Walther, 2018;Avigliano et al, 2019). Although scale and fin spine resorption through life is well-documented, chemical stability in the marginal area has been observed, making it a suitable tool for stock identification in some fishes (e.g., Avigliano et al, 2020b).…”
Section: Chemically Alterable Structuresmentioning
confidence: 99%